2003
DOI: 10.1038/sj.bjc.6601396
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, mechanism and prognostic value of activated AKT in pancreas cancer

Abstract: When activated, the serine/threonine kinase AKT mediates an antiapoptotic signal implicated in chemoresistance of various cancers. The mechanism(s) of AKT activation are unknown, though overexpression of HER-2/neu has been implicated in breast cancer. Therefore, we determined the incidence of activated AKT in human pancreatic cancer, whether HER-2/neu is involved in AKT activation, and if AKT activation is associated with biologic behaviour. HER-2/neu expression and AKT activation were examined in seven pancre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
151
0
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(165 citation statements)
references
References 28 publications
(34 reference statements)
9
151
0
5
Order By: Relevance
“…In addition, Akt activation due to phosphorylation of Akt protein at Thr308 or Ser473 also augments cellular resistance to various treatments. [9][10][11] Based on the notion that inhibition of constitutively active Akt and NF-jB signaling may attenuate chemo-resistance, hence strategies specifically targeting the inhibition of NF-jB and Akt have emerged as an alternative and attractive therapeutic arsenal for cancer treatment. [12][13][14][15] In recent years, naturally occurring compounds in the diet have gained considerable attention because of their alleged beneficial effects as chemopreventive agents, partly attributable to dual inactivation of NF-jB and Akt signaling cascade.…”
mentioning
confidence: 99%
“…In addition, Akt activation due to phosphorylation of Akt protein at Thr308 or Ser473 also augments cellular resistance to various treatments. [9][10][11] Based on the notion that inhibition of constitutively active Akt and NF-jB signaling may attenuate chemo-resistance, hence strategies specifically targeting the inhibition of NF-jB and Akt have emerged as an alternative and attractive therapeutic arsenal for cancer treatment. [12][13][14][15] In recent years, naturally occurring compounds in the diet have gained considerable attention because of their alleged beneficial effects as chemopreventive agents, partly attributable to dual inactivation of NF-jB and Akt signaling cascade.…”
mentioning
confidence: 99%
“…Nave et al (13) found that Akt/protein kinase B regulates the phosphorylation state of mTOR directly. Akt, an apoptotic regulator, is frequently activated in pancreatic cancer (14). Although rapamycin is not considered to be an antiapoptotic factor, a recent publication established Akt signaling through mTOR and eIF-4E as an important mechanism of oncogenesis and drug resistance in vivo by proving that rapamycin can restore apoptotic sensitivity to lymphomas expressing Akt in vivo (15).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of miR-146 is further underscored by its upregulation evidenced in a number of epithelial tumors . Interestingly, activated NF-kB signalling has been demonstrated in PDAC and is likely the result of an activated phosphatidylinositol 3-OH kinase (PI3K)/AKT signalling pathway (Altomare et al, 2003;Schlieman et al, 2003). It will be important to identify and test miR-146 downstream target genes, such as NUMB, SP8 or KLF7 (Supplementary Table 6), to gain insights into the signalling pathways altered by the aberrant expression of this miRNA.…”
Section: Discussionmentioning
confidence: 99%